PELATIHAN PEMBUKUAN PRAKTIS BAGI PENGUSAHA RABUK HARUAN KECAMATAN BANJARMASIN UTARA KOTA BANJARMASIN - Ferra Maryana; Masrifani Masrifani (Universitas Islam kalimantan MAB, 2018)
Rabuk haruan is a famous Banjarmasin culinary commodity. Rabuk haruan is also product of creative economy in culinary sub sector. But in practice, the owner of this enterprise especially in Banjarmasin Utara had not knew about their enterprise progress. It happened because of they never made ledger and report by continuity. That is why they need book keeping training to increase their competence that impact their ability to know their finance performance. The result showed there was difference value before and after the training with significance value is 0,000. Therefore, it still need the BUM and government involvement to improved rabuk haruan performance.